2017
DOI: 10.1155/2017/4104137
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptor Antagonist and Interleukin-4 Genes Variable Number Tandem Repeats Are Associated with Adiposity in Malaysian Subjects

Abstract: Interleukin-1 receptor antagonist (IL1RA) intron 2 86 bp repeat and interleukin-4 (IL4) intron 3 70 bp repeat are variable number tandem repeats (VNTRs) that have been associated with various diseases, but their role in obesity is elusive. The objective of this study was to investigate the association of IL1RA and IL4 VNTRs with obesity and adiposity in 315 Malaysian subjects (128 M/187 F; 23 Malays/251 ethnic Chinese/41 ethnic Indians). The allelic distributions of IL1RA and IL4 were significantly different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It was recently discovered that IL‐22 is associated with obesity and type 2 diabetes . Variants in the gene encoding IL‐1RA have also been linked to adiposity …”
Section: Discussionmentioning
confidence: 99%
“…It was recently discovered that IL‐22 is associated with obesity and type 2 diabetes . Variants in the gene encoding IL‐1RA have also been linked to adiposity …”
Section: Discussionmentioning
confidence: 99%
“…Another study of CLOCK SNPs reported that three SNPs were associated with plasma cytokine levels, especially IL-6, adiponectin, and CCL2/MCP-1 [86]. Separately, variable number tandem repeats (VNTRs), such as 86 bp repeats in IL-1 receptor antagonist (IL-1RA) intron 2 and 70 bp in IL-4 intron 3, were reported to be associated with obesity and adiposity in a Malaysian study [87]. Apolipoprotein ApoA-IV, found on high-density lipoproteins (HDL) cholesterol in serum, as well as in circulation, is known to have anti-inflammatory effects.…”
Section: Circadian Rhythm In Allergymentioning
confidence: 99%
“…With regard to obesity, two previous Asian studies with relatively small sample sizes found no significant association between IL1RA VNTR and BMI in Koreans [ 200 ] and North Indians [ 201 ]. Similarly, our study found no association with BMI value or overall obesity status, but IL1RA II allele VNTR was associated with higher TBF value and higher risk for overall adiposity [ 202 ].…”
Section: Main Textmentioning
confidence: 78%
“…With regard to obesity, there are limited studies on this VNTR, where two studies showed no association [ 215 , 216 ]. Our study showed that this VNTR was associated with overall adiposity status (TBF class), but not with TBF value after adjustment for ethnicity [ 202 ]. A previous study in north Indians also showed that the B2B2 genotype was associated with higher risk for T2D [ 217 ].…”
Section: Main Textmentioning
confidence: 99%